2011
DOI: 10.1002/rcm.5072
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic investigation of cholestasis in a rat model using ultra‐performance liquid chromatography/tandem mass spectrometry

Abstract: Metabolomics follows the changes in concentrations of endogenous metabolites, which may reflect various disease states as well as systemic responses to environmental, therapeutic, or genetic interventions. In this study, we applied metabolomic approaches to monitor dynamic changes in plasma and urine metabolites, and compared these metabolite profiles in Eisai hyperbilirubinemic rats (EHBR, an animal model of cholestasis) with those in the parent strain of EHBR - Sprague-Dawley (SD) rats - in order to characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
(19 reference statements)
4
16
0
Order By: Relevance
“…The method includes the simultaneous quantifi cation Serum and tissue liver sample preparation Most methods used to target BAs in serum involve the removal of proteins by precipitation using organic solvents, followed by a solid-phase extraction (SPE) ( 12,22,24,(28)(29)(30)(31)(32)(33). On the other hand, preparation of liver tissue involves a homogenization step, usually followed by an SPE step ( 17,34 ).…”
Section: The Uplc-mrm-ms Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The method includes the simultaneous quantifi cation Serum and tissue liver sample preparation Most methods used to target BAs in serum involve the removal of proteins by precipitation using organic solvents, followed by a solid-phase extraction (SPE) ( 12,22,24,(28)(29)(30)(31)(32)(33). On the other hand, preparation of liver tissue involves a homogenization step, usually followed by an SPE step ( 17,34 ).…”
Section: The Uplc-mrm-ms Methodsmentioning
confidence: 99%
“…The patterns of BAs that we obtained in serum samples from each species are in good agreement with those reported by other authors. However, our method provides a more specifi c and comprehensive profi ling of BAs in rodents than previous reports in which ␣ -, ␤ -, and -MCA, and their taurine conjugates were not properly quantifi ed ( 12,23,31 ). The results are expressed in nM as mean ± SD (n = 8).…”
Section: Bile Acids Profi Ling In Human Rat and Mouse Serum And In mentioning
confidence: 96%
See 1 more Smart Citation
“…Metabolomics revealed that cholestasis induced in Fxr -null mice by a cholic acid diet resulted in increased urinary excretion of bile salt tetrols, predominantly 3α,6,7α,12α-tetrahydroxy-5β-cholestan-26-oyltaurine, due to an adaptive upregulation of the steroid-hydroxylating cytochrome P450 CYP3A11 in these mice [99]. An adaptive response was also characterized in a rat cholestasis model, with a shift from cytotoxic to cytoprotective bile acids in plasma and urine [100]. …”
Section: The Metabolomic Window Into Other Hepatobiliary Diseasesmentioning
confidence: 99%
“…Ultra‐performance liquid chromatography (UPLC) operates with sub‐2 μm packed columns and a fluid system capable of operating at higher pressure, providing better peak resolution, higher sensitivity and fast speed for complex mixture separation compared with conventional high‐performance liquid chromatography (HPLC) . The combination of UPLC and quadrupole time‐of‐flight mass spectrometry has been one of the predominant analytical platforms for identification of the constituents of natural products and metabolites …”
Section: Introductionmentioning
confidence: 99%